2016
DOI: 10.18869/acadpub.johe.5.4.202
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mental workload and work posture on musculoskeletal disorders of Qazvin hospitals, in 2016

Abstract: Background: Due to high prevalence of musculoskeletal risk factors among kitchen workers and their role in causing discomfort, the aim of this study was to investigate the effects of ergonomic factors (mental workload and working posture) on musculoskeletal disorders (MSDs) among workers of training hospitals in Qazvin, Iran. Materials and Methods: This cross-sectional study was done through census among 60 workers of teaching hospital's kitchens of Qazvin University of Medical Sciences in 2016. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 6 publications
1
11
0
1
Order By: Relevance
“…A total of 8883 respondents were participated from 14 different countries. Five studies were conducted from India [ 11 , 24 , [27] , [28] , [29] ], four from Ethiopia [ 1 , 8 , 20 , 21 ], three from Iran [ 26 , 30 , 31 ], two from China [ 25 , 32 ], two from Malaysia [ 7 , 33 ], and one study each from Bangladesh [ 4 ], Egypt [ 9 ], Saudi Arabia [ 34 ], Ghana [ 23 ], Pakistan [ 35 ], Kuwait [ 6 ], Nigeria [ 36 ], Sri Lanka [ 37 ], and Estonia [ 38 ]. The prevalence of WMSDs was obtained from all studies [ 1 , 4 , [6] , [7] , [8] , [9] , 11 , 20 , 21 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], while the data regarding to associated factors were also reported by all except two studies [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8883 respondents were participated from 14 different countries. Five studies were conducted from India [ 11 , 24 , [27] , [28] , [29] ], four from Ethiopia [ 1 , 8 , 20 , 21 ], three from Iran [ 26 , 30 , 31 ], two from China [ 25 , 32 ], two from Malaysia [ 7 , 33 ], and one study each from Bangladesh [ 4 ], Egypt [ 9 ], Saudi Arabia [ 34 ], Ghana [ 23 ], Pakistan [ 35 ], Kuwait [ 6 ], Nigeria [ 36 ], Sri Lanka [ 37 ], and Estonia [ 38 ]. The prevalence of WMSDs was obtained from all studies [ 1 , 4 , [6] , [7] , [8] , [9] , 11 , 20 , 21 , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ], while the data regarding to associated factors were also reported by all except two studies [ 27 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…The prevalence of MSDs was highest (95.3 %) and lowest (33.8 %) in Shah Alam, Malaysia [ 33 ] and Tamil Nadu, India [ 11 ] respectively as shown in Table 1 . According to Table 2 , fifteen out of twenty-five studies reported that the lower back, neck, upper back, and shoulder were the most affected body parts, and the elbow, hip/thigh, knee, wrist/hand, and ankle/feet were the least affected body parts, respectively [ 1 , 4 , [6] , [7] , [8] , 11 , [20] , [21] , [22] , [23] , 25 , 28 , 30 , 31 , 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tais dados corroboram com os achados por Ansari et al (2016), que ao investigarem a percepção da carga mental em operadores de uma cozinha hospitalar, encontraram um relato de 85% dos trabalhadores que entendiam seu turno de trabalho mais pesado que o normal. As percepções sobre o estresse no trabalho foram relacionadas ao desenvolvimento de artrite e dores na coluna segundo revisão da literatura desenvolvida por Buscemi et al (2019).…”
Section: Resultsunclassified
“…Beside these physical effects of a standing working position, we assume that a high workload is associated with a less relaxed posture and a higher stress level, both increasing the risk for pain (Nino et al. 2019 ; et al., Ansari et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%